Analysis of Heavy Metal Concentrations of Lead (Pb) in Fishermen in Junganyar Village Based on Length of Work Using Atomic Absorption Spectrophotometer Method - Muallimil Husna; Galuh Ratmana Hanum (Indonesian Journal of Cultural and Community Development, 2023)
Heavy metals are natural components that cannot be destroyed. Lead (Pb) in the oceans comes from activities from ship repair, mining activities, shipbuilding, land and sea transportation activities, to household and urban waste. This study was conducted to determine the levels of lead (Pb) in urine and their relationship to the working period of fishermen. This study used an experimental type of research with 16 urine samples and was carried out in June-July 2022 at the Chemistry Laboratory of the Technology Study Program, the Medical Laboratory of the University of Muhammadiyah Sidoarjo and the FMIPA Laboratory of UIN Maulana Malik Ibrahim Malang. Examination using SSA measurement. The data analysis method used the Pearson and Spearman correlation statistical test. Pearson correlation test obtained a correlation coefficient value of lead (Pb) of 0.208 (positive value for the category of very weak correlation) with a significance of 0.439, so it can be concluded that there is no relationship between heavy metals lead (Pb) in urine with fisherman's tenure.